1: Thay x=9 vào A, ta được:
\(A=\dfrac{\sqrt{9}-1}{\sqrt{9}}=\dfrac{3-1}{3}=\dfrac{2}{3}\)
2: \(B=\dfrac{\sqrt{x}}{\sqrt{x}-1}-\dfrac{1}{x-\sqrt{x}}\)
\(=\dfrac{\sqrt{x}}{\sqrt{x}-1}-\dfrac{1}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(=\dfrac{x-1}{\sqrt{x}\left(\sqrt{x}-1\right)}=\dfrac{\left(\sqrt{x}-1\right)\left(\sqrt{x}+1\right)}{\sqrt{x}\left(\sqrt{x}-1\right)}\)
\(=\dfrac{\sqrt{x}+1}{\sqrt{x}}\)
3: P=B:A
\(=\dfrac{\sqrt{x}+1}{\sqrt{x}}:\dfrac{\sqrt{x}-1}{\sqrt{x}}\)
\(=\dfrac{\sqrt{x}+1}{\sqrt{x}}\cdot\dfrac{\sqrt{x}}{\sqrt{x}-1}=\dfrac{\sqrt{x}+1}{\sqrt{x}-1}\)
\(=\dfrac{\sqrt{x}-1+2}{\sqrt{x}-1}=1+\dfrac{2}{\sqrt{x}-1}\)
Để P lớn nhất thì \(\dfrac{2}{\sqrt{x}-1}+1\) lớn nhất
=>\(\dfrac{2}{\sqrt{x}-1}\) lớn nhất
=>\(\sqrt{x}-1\) là số nguyên dương nhỏ nhất
=>\(\sqrt{x}-1=1\)
=>\(\sqrt{x}=2\)
=>x=4(nhận)